Bioavailability and bioequivalence in pharmaceutical technology - Pal, Tapan Kumar;Ganesan, M. (New Delhi, India : CBS Publishers & Distributors, 2004)
Proceedings of the Seminar-cum-Workshop on Bioavailability and Bioequivalence.
Ethical issues involved in Bioequivalence study -- Understanding bioavailability -- Bioavailability studies in man: pharmacokinetic considerations -- Method of sample preparation and HPLC analysis of some common drugs from biological fluids -- Application of HPLC for analysis of biological samples and drugs -- Microdialysis and its application in bioavailability studies -- Ocular kinetics and drug delivery systems of ophthalmic medicines- a review -- Bioequivalence study and data interpretation -- Introduction to bio-analytical method development and validation for bioavailability and bio-equivalence studies -- High performance liquid chromatography, an upgraded technology for the monitoring of therapeutic drugs -- Systematic clinical and toxicological analysis using solid phase extraction -- Bioequivalence of Gatifloxacin by HPLC method- a case study
Includes bibliographical references.
Keywords: DRUGS BIOAVAILABILITY